Data and the new oil: Cloud computing's lubrication of the petrotechnical. Issue 2 (1st December 2021) - Munn, Luke
Sophisticated modelling and machine learning technologies, underpinned by cloud computing, are increasingly being deployed within the oil and gas industry. As the easy energy pockets of the past dry up, such technologies promise to locate deposits, increase extraction and optimize production. These high-performance computing technologies require vast infrastructures, a requirement that, in the midst of a climate crisis, has seen a new alliance between Big Tech and Big Oil. Drawing on grey literature from press releases to whitepapers and tech demonstrations, this article investigates these alliances between oil companies and tech companies, along with the rise of cloud-driven processes in energy discovery and production ‐ in short, the new intersection between the computational and the petrotechnical. How might the extractive violence of the 'petro' be intensified and diversified by the 'technical' of cloud computing? It argues that cloud computing does indeed contribute to more efficient processes of energy extraction, but that this effectively means an optimization of ecological destruction, assisting the industry in more rapidly and comprehensively damaging diverse forms of life. Understanding the logics of these technologies and the political economy that underpins them is crucial for intervening effectively against these environmentally devastating operations.